Pengaruh Celebrity Endorsement, EWOM, dan Limited Edition Product Terhadap Purchase Intention - Agustin, Tika; Hakim, Abdurrahman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to identify the effects of Song Joong-ki’s celebrity endorsement, electronic word-of-mouth, and Song Joong-ki limited edition product on the intention of Indonesian Generation Z to purchase Scarlett Whitening. This explanatory research elucidates and proves the relationship between independent and dependent variables. Using non-probability sampling method and purposive sampling technique, 250 people were selected as the respondents. The data of this study was harvested from Google Forms questionnaires and was analyzed using multiple linear regression in SPSS version 29. This study finds that Song Joong-ki’s celebrity endorsement positively yet insignificantly influences the purchase intention, that electronic word-of-mouth positively and significantly influences the purchase intention, and that Song Joong-ki limited edition product positively and significantly impacts the purchase intention. Furthermore, Song Joong-ki’s celebrity endorsement, electronic word-of-mouth, and Song Joong-ki limited edition product simultaneously do not contribute to the purchase intention. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh celebrity endorsement Song Joong-ki, electronic word of mouth dan Song Joong-ki limited edition product terhadap purchase intention generasi z pada Scarlett Whitening di Indonesia. Jenis penelitian ini adalah explanatory research yang menjelaskan atau membuktikan hubungan atau pengaruh antar variabel independen dan dependen. Penelitian ini menggunakan sampel sebanyak 250 responden dimana penyebaran kuesioner dilaksakan menggunakan google form. Pengambilan sampel menggunakan metode non-probability sampling dengan teknik purposive sampling. Analisis data menggunakan Analisis Regresi Linier Berganda dengan menggunakan SPSS ver. 29. Hasil analisis yang didapat dalam penelitian ini adalah celebrity endorsement Song Joong-ki memiliki pengaruh yang positif namun tidak signifikan terhadap purchase intention, electronic word of mouth berpengaruh positif dan signifikan terhadap purchase intention, Song Joong-ki limited edition product berpengaruh positif dan signifikan terhadap purchase intention, dan celebrity endorsement Song Joong-ki, electronic word of mouth, Song Joong-ki limited edition product secara bersama-sama tidak memiliki kontribusi terhadap Purchase Intention.